Designed Synthesis and Catalytic Mechanisms of Non‐Precious Metal Single‐Atom Catalysts for Oxygen Reduction Reaction. Issue 10 (13th September 2021) - Tong, Miaomiao; Wang, Lei; Fu, Honggang
Abstract: Oxygen reduction reaction (ORR) is the important half‐reaction for metal–air batteries and fuel cells (FCs), which plays the decisive role for the performance of whole devices. Developing high‐efficiency non‐precious metal ORR catalysts is urgent and still challenging. Single‐atom catalysts (SACs) are considered to be one of the promising substitutes for Pt due to their maximum atom utilization efficiency and mass activity. Despite considerable efforts in preparing various SACs, the reaction mechanism and intrinsic activity modulation during the ORR reaction are still not understood in‐depth. In this review, the latest advances in the current synthetic strategies for SACs are summarized. The effect of various coordination environments including central metal atoms, coordination atoms, environmental atoms, and guest groups on the intrinsic ORR activity of SACs are discussed. The electrocatalytic mechanisms are clarified by combining density functional theory calculations with in situ advanced characterization technologies. Then, the applications of SACs in FCs and Zn–air batteries are reviewed. Finally, the prospects and challenges for further development of SACs are highlighted. Abstract : The advances of synthetic strategies, catalytic mechanisms, and intrinsic activity regulations of transition metal single atom catalysts (SACs) for oxygen reduction reaction, are discussed. The research progress of SACs applied in significant energy devices includes fuel cells and Zn–air batteries are clarified and analyzed.